2004
DOI: 10.1002/gps.1111
|View full text |Cite
|
Sign up to set email alerts
|

Childlessness and psychological well‐being in Chinese older adults

Abstract: The impact of childlessness on psychological well-being among elderly Chinese is more robust than that found in older Americans. Moreover, consistent with the findings of previous studies, we found that the effect of childlessness on psychological well-being has to be investigated in the context of marital status. Therefore, aged care service practitioners must take this risk factor into consideration in their preventive intervention and treatment for psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 46 publications
7
73
4
Order By: Relevance
“…Moreover delaying age at marriage was a key to improving women's status and may be a way of increasing their leverages in the decision-making process. This was in accordance with Chou (2004) who stated that, the impact of childlessness on psychological well-being among elderly Chinese is more robust than that found in older Americans. [1] Regarding the duration of marriage among infertile women, the present study revealed that 73.4% of the study subjects were less than 5 years while 26.6% of them were more than 5 years.…”
Section: Published By Sciedu Presssupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover delaying age at marriage was a key to improving women's status and may be a way of increasing their leverages in the decision-making process. This was in accordance with Chou (2004) who stated that, the impact of childlessness on psychological well-being among elderly Chinese is more robust than that found in older Americans. [1] Regarding the duration of marriage among infertile women, the present study revealed that 73.4% of the study subjects were less than 5 years while 26.6% of them were more than 5 years.…”
Section: Published By Sciedu Presssupporting
confidence: 91%
“…This appears in part of some women who tend to defer child birth until the mid to late 30s and the associated decrease in fertility after the age of 35. [1,2] In contrast, in the developing world, at that place is a little voluntary effort to delay childbearing and early first marriage is common. [3] Infertility or failure to achieve pregnancy is a universal phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have focused on the difference between childless older people and older parents in terms of their psychological well-being in areas such as loneliness and depression (Chou & Chi, 2004;Koropeckyj-Cox, 1998;Z. Zhang & Hayward, 2001); their social contacts (Grundy & Read, 2012), social integration (Dykstra, 2006;McMullin & Marshall, 1996), and social support and networks (Albertini & Mencarini, 2014;Gironda, Lubben, & Atchison, 1999;Larsson & Silverstein, 2004).…”
Section: Overviewmentioning
confidence: 99%
“…Examples were from China (Chou & Chi, 2004;W. Zhang & Liu, 2007) and Indonesia (Schröder-Butterfill & Kreager, 2005).…”
Section: Previous Studies On Childlessnessmentioning
confidence: 99%
See 1 more Smart Citation